THE RELATIONSHIP BETWEEN ORGANIZATIONAL FACTORS AND THE SUCCESS OF SUGGESTION SYSTEM (CAHIERS MAGELLANES-NS, 2024)
The aim of this research study was to identify the organisational factors such as Organisation culture, organisation climate, top management involvement and supervisor support. The success of suggestion system is measured in terms of the active participation of employees in suggestion scheme . Data were collected using questionnaire from a random of 180 employees working in Automobile Industry in India. The findings of the analysis indicates that all four organisational factors significantly influence the employee participation in suggestion system.